1997
DOI: 10.1097/00003246-199708000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxemia and reoxygenation with 21% or 100% oxygen in newborn piglets

Abstract: Significantly higher extracellular concentrations of hypoxanthine were found in the cerebral cortex during the initial period of reoxygenation with 100% oxygen compared with 21% oxygen. Hypoxanthine is a marker of hypoxia, and reflects the intracellular energy status. These results therefore suggest a possibly more severe impairment of energy metabolism in the cerebral cortex or an increased blood-brain barrier damage during reoxygenation with 100% oxygen compared with 21% oxygen in this newborn piglet hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Several studies from our group, both animal and clinical [1][2][3][4][5][6], have shown that resuscitation with 21% O 2 may be as efficacious as 100% O 2 . In a piglet model of global hypoxemia, no significant differences in mean arterial blood pressure (MABP), base deficit, hypoxanthine in plasma, brain morphology, cerebral blood flow or extracellular levels of hypoxanthine and excitatory amino acids in the brain had been found after reoxygenation with 21% O 2 compared with 100% O 2 [1][2][3][4]. However, in a recent study, we have changed our experimental model of asphyxia in newborn piglets from global hypoxemia to combined cerebral hypoxemia-ischemia (HI) [7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several studies from our group, both animal and clinical [1][2][3][4][5][6], have shown that resuscitation with 21% O 2 may be as efficacious as 100% O 2 . In a piglet model of global hypoxemia, no significant differences in mean arterial blood pressure (MABP), base deficit, hypoxanthine in plasma, brain morphology, cerebral blood flow or extracellular levels of hypoxanthine and excitatory amino acids in the brain had been found after reoxygenation with 21% O 2 compared with 100% O 2 [1][2][3][4]. However, in a recent study, we have changed our experimental model of asphyxia in newborn piglets from global hypoxemia to combined cerebral hypoxemia-ischemia (HI) [7].…”
Section: Introductionmentioning
confidence: 94%
“…Microdialysis probes (CMA 10, CMA, Stockholm, Sweden) with a membrane length of 4 mm and a molecular mass cutoff of 20,000 D were perfused at 3 Ìl/min with an unbuffered electrolyte solution as previously described [4]. Samples for measurement of hypoxanthine were collected at 20-min intervals.…”
Section: Microdialysismentioning
confidence: 99%
“…In this and a series of subsequent experiments, we confirmed that 21% oxygen is as efficient as 100% oxygen for resuscitation. [10][11][12][13][14][15][16] The findings in the newborn piglet were consistent, and I realized that the time had come to test our hypothesis in a clinical study. Siddarth Ramji in New Delhi immediately agreed to participate, and the pilot clinical trial was carried out in India, enrolling 84 newborn infants randomized to room air or 100% oxygen resuscitation.…”
Section: Discovery Through a Failurementioning
confidence: 55%
“…A three-fold volume of 0.9% sodium chloride replaced the withdrawn blood. Hypoxanthine concentration in plasma was analyzed by HPLC as previously described (14).…”
Section: Tølløfsrud Et Almentioning
confidence: 99%
“…However, in the last few years, several animal studies (12)(13)(14)(15) and two clinical studies (4,5) have shown that resuscitation with room air is as efficient as resuscitation with 100% oxygen, and the World Health Organization's new guidelines for resuscitation now recommend the use of room air for basic resuscitation of asphyxiated newborns without MA (16). We wished to test the hypothesis that room air is as efficient as 100% O 2 for reoxygenation even after MA, because the latter is the most important cause of lung problems during resuscitation of newborns.…”
mentioning
confidence: 99%